2011
DOI: 10.1007/s00427-011-0356-6
|View full text |Cite
|
Sign up to set email alerts
|

Getting real with real-time qPCR: a case study of reference gene selection for morphological variation in Drosophila melanogaster wings

Abstract: Accurate estimation of gene expression differences during development requires sensitive techniques combined with gold-standard normalization procedures. This is particularly true in the case of quantitative traits, where expression changes might be small. Nevertheless, systematic selection and validation of reference genes has been overlooked, even in Drosophila studies. Here, we tested the stability of six traditional reference genes across samples of imaginal wing disks from morphologically divergent strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 21 publications
(45 reference statements)
2
17
0
Order By: Relevance
“…Discrepancies between NormFinder and geNorm were also demonstrated by other studies [4], [5], [32], [52]. This approach could be problematic if co-regulated genes exhibit similar expression profiles and thus, might be preferentially top ranked [24]. Under viral stress, we found that the UBC21 / UPL7 pair was identified as the most stable by geNorm, followed by UBC9 .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Discrepancies between NormFinder and geNorm were also demonstrated by other studies [4], [5], [32], [52]. This approach could be problematic if co-regulated genes exhibit similar expression profiles and thus, might be preferentially top ranked [24]. Under viral stress, we found that the UBC21 / UPL7 pair was identified as the most stable by geNorm, followed by UBC9 .…”
Section: Discussionsupporting
confidence: 73%
“…It is generally assumed that housekeeping genes encoding proteins required for basal cell activities, such as central carbon metabolism, protein translation, cytoskeleton maintenance, and protein turnover, are expressed uniformly in different tissues and organs [6]. However, under many conditions, the level of transcript expressed from such genes was not stable, which may have led to the misinterpretation of results [20][24]. Statistical algorithms such as geNorm [25] and NormFinder [26] have been recently used to identify the best reference genes for RT-qPCR data normalization in a given set of biological samples.…”
Section: Introductionmentioning
confidence: 99%
“…All amplifications and fluorescence quantifications were performed by a Bio-Rad Chromo 4 real-time PCR Detector (Bio-Rad). A ΔΔCt-based method was used to analyze atg8 levels and the gst gene of B. malayi or the RP49 gene of Drosophila for normalization (10,41,42). All comparisons were replicated with at least three biological repeats with three technical replicates for each repeat.…”
Section: Methodsmentioning
confidence: 99%
“…In the Tephritidae family there are two studies on the oriental fruit fly, Bactrocera dorsalis 1718 and one in the West Indian fruit fly Anastrepha obliqua 19. Among other dipteran species, there are three studies on Drosophila melanogaster 152021 and a single one on each of D. suzukii 22, Musca domestica 23, Lucilia cuprina 24 and the Calliphoridae family25. Interestingly, there are no studies published on any mosquito species.…”
mentioning
confidence: 99%
“…Most frequently, however, there is no specific justification regarding the selection of the utilized HKGs28293031323334 except, at most, that it may have been used previously in the same3536 or related species3738. Furthermore, with regard to published HKG studies on Diptera, the number of HKGs tested varies from as low as six182125 to over 2015. Unfortunately, neither the same genes nor the same tissues and conditions are studied, a fact that makes any effort to compare results practically impossible.…”
mentioning
confidence: 99%